2018
DOI: 10.1080/15438627.2018.1492392
|View full text |Cite
|
Sign up to set email alerts
|

Effects of traditional balance and slackline training on physical performance and perceived enjoyment in young soccer players

Abstract: The aim of this study was to evaluate the effects of 12-week balance and slackline training programs on physical performance and perceived enjoyment scale in young soccer players. Forty-one preadolescent soccer players were assigned to two experimental groups performing traditional balance (BLT) or slackline training (SLT), and a control group. Pre-post assessment encompassed Balance Error Scoring System (BESS), Star Excursion Balance test (SEBT), sprint with 90° turns (S90), and countermovement jump (CMJ). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 28 publications
1
29
0
5
Order By: Relevance
“…Increasing the training volume and/or the total training duration could potentially lead to a transfer to untrained tasks. Recently, a study showed that after 12 weeks of slackline training, young soccer players were better than a control group in untrained balance tasks, indicating a possible transfer effect induced by the training [ 27 ]. More long-term training studies are necessary to understand the generalization effect induced by balance training.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the training volume and/or the total training duration could potentially lead to a transfer to untrained tasks. Recently, a study showed that after 12 weeks of slackline training, young soccer players were better than a control group in untrained balance tasks, indicating a possible transfer effect induced by the training [ 27 ]. More long-term training studies are necessary to understand the generalization effect induced by balance training.…”
Section: Discussionmentioning
confidence: 99%
“…All individuals wore the same clothing and footwear throughout the testing session. All subjects recovered 10 min between each test to avoid fatigue-induced effects ( Trecroci et al, 2020 ; Trecroci et al, 2018a ; Trecroci et al, 2018b ; Trecroci et al, 2018c ). An electronic timing gates system (Microgate, Bolzano, Italia) was used to measure the sprint and COD performance time ( Trecroci et al, 2020 ; Trecroci et al, 2018a ; Trecroci et al, 2018b ; Trecroci et al, 2018c ).…”
Section: Methodsmentioning
confidence: 99%
“…The experimental protocol lasted 5 weeks, in which the CMPT group underwent 2 sessions per week of compound training, whereas the CNT group underwent 2 sessions per week (e.g., on Tuesday and Thursday) of soccer-specific training (10 sessions in total for each group). Both CMPT and CNT performed an identical third weekly session (e.g., on Friday) based on soccer-related drills [20] and a soccer match at the end of the week (48 h from the last training session). Of note, the two sessions per week of both interventions (CMPT and CNT) were arranged at the same time of day and matched for the same amount of time.…”
Section: Experimental Protocolmentioning
confidence: 99%